Ankle–Brachial Index: An Ubiquitous Marker of Cognitive Impairment—The EPIDEMCA Study. (July 2018) - Desormais, Ileana; Aboyans, Victor; Guerchet, Maëlenn; Ndamba-Bandzouzi, Bébène; Mbelesso, Pascal; Mohty, Dania; Marin, Benoît; Dartigues, Jean Francois; Preux, Pierre-Marie; Lacroix, Philippe; ,
Epidemiological research on the implication of atherosclerosis in the development of cognitive impairment is lacking in low- and middle-income countries, where two-thirds of the individuals affected by dementia live. Individuals aged ≥65 years living in urban and rural areas of 2 countries in Central Africa were invited. Demographic, clinical, and biological data were collected, and the ankle–brachial index (ABI) was measured. Cognitive impairment was defined according to the Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) criteria. Among 1662 participants (age 72.9 years, 59.3% females), the prevalence of cognitive impairment was 13.6%, which is higher in individuals with ABI ≤ 0.90 and ABI ≥ 1.40 than those with 0.90 < ABI < 1.40 (20.1% and 17% vs 12%, P = .0024). Cognitive impairment was significantly associated with the factors such as age (odds ratio [OR]: 1.09; 95% confidence interval [CI]: 1.07-1.12, P < .0001), female gender (OR: 2.36, 95% CI: 1.59-3.49, P < .0001), smoking (OR: 1.54, 95% CI: 1.06-2.23, P = .0026), and low ABI (≤0.90; OR: 1.52, 95% CI: 1.03-2.25, P = .0359). The ABI, a ubiquitous marker of atherosclerosis, provides independent and incremental information on susceptibility to present with cognitive disorders.